2011
DOI: 10.1111/j.1471-0528.2011.03004.x
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric outcome in women with epilepsy: a hospital-based, retrospective study

Abstract: Objective To report the complications during pregnancy and delivery in women with epilepsy, compared with a control group without epilepsy, with special focus on potential risk factors, such as epilepsy severity and dosage of antiepileptic drugs.Design Hospital-based retrospective study.Setting Data from pregnancy notification forms and hospital case records.Population Women with a past or present history of epilepsy (n = 205) delivered in Bergen, Norway, in the period 1999-2006, and a matched control group of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
56
4
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 50 publications
(132 reference statements)
6
56
4
4
Order By: Relevance
“…However, a previous study did not find any association between seizure activity and complications in pregnancy (3). However, a previous study did not find any association between seizure activity and complications in pregnancy (3).…”
Section: Discussionmentioning
confidence: 81%
“…However, a previous study did not find any association between seizure activity and complications in pregnancy (3). However, a previous study did not find any association between seizure activity and complications in pregnancy (3).…”
Section: Discussionmentioning
confidence: 81%
“…Higher rate of CS has also been observed in other chronic conditions [32][34] and it has been proposed that the higher rates of delivery interventions might be related to foetal stress associated with the underlying disease. However, we did not find an association between asthma and low Apgar score or child hypoxia or asphyxia in the registers.…”
Section: Discussionmentioning
confidence: 92%
“…Previous research suggests a moderately increased risk of bleeding in late pregnancy, as well as during and after delivery for WWE using AED . In a hospital‐based study, WWE had significantly more bleeding in early pregnancy , whereas a population‐based study showed no difference . Some studies have reported no excess of these outcomes in WWE .…”
Section: Discussionmentioning
confidence: 92%
“…On the other hand, recent studies have suggested an increased risk of premature delivery limited to WWE using AED . Nonetheless, there are contradictory results suggesting a higher risk of premature delivery only for WWE without AED .…”
Section: Discussionmentioning
confidence: 99%